Comparing regional Australian fruit and vegetable prices according to growing location and retail characteristics - Carmen Vargas; Kathryn Backholer; Jacqueline Monaghan; Kate Parker; Chanel Relf; Todd Wallace; Julian Fang; Christina Zorbas (Australian and New Zealand Journal of Public Health, 2025)
Objectives: To understand how fruit and vegetable prices in regional Victoria, Australia, vary depending on growing location, retailer type, socioeconomic area and remoteness level. Methods: A feasibility study was conducted to collect and examine fruit and vegetable prices in Loddon Campaspe based on growing location and store characteristics. Statistical analyses were used to test the significance of price differences according to these area-level characteristics. Results: Fruit and vegetable prices were collected from 65 vendors between February and May 2023. Fruit or vegetable options were typically similar in price when locally grown compared to when grown elsewhere but were often cheapest at large supermarkets. No consistent relationships were found between fruit and vegetable prices and area-level socioeconomic position or remoteness. Conclusions: With the exception of fruit and vegetable prices often being cheaper at supermarkets than small retailers, no other consistent relationships were observed in the context of our study. Implications for Public Health: Addressing fruit and vegetable prices and their affordability, including through policies and research that target small retailers, income supports, and localised food systems initiatives are likely to be important leverage points to reduce regional inequities in access to healthy diets in Victoria.